Silane-crosslinked acrylic rubber molded article and its manufacturing method, silane-crosslinkable acrylic rubber composition, and silane-crosslinked acrylic rubber molded article
Patent Information
- Application Number
- JP2021058369
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-03-30
AI Technical Summary
【0012】 本発明は、優れた外観、高温耐油性、機械特性、及び柔軟性を兼ね備え、ブリードの抑制されたシラン架橋アクリルゴム成形体を得ることができる製造方法、この製造方法によって得られたシラン架橋アクリルゴム成形体、及びシラン架橋アクリルゴム成形品を提供できる。また、このような優れた特性を示すシラン架橋アクリルゴム成形体の製造に好適な、シラン架橋性アクリルゴム組成物を提供できる。
Smart Images

Figure 0007640333000001 
Figure 0007640333000002 
Figure 0007640333000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a silane-crosslinked acrylic rubber molded article and a method for producing the same, a silane-crosslinkable acrylic rubber composition, and a silane-crosslinked acrylic rubber molded article. [Background technology]
[0002] Various properties, such as mechanical properties (e.g., tensile strength, tensile elongation), flexibility, and appearance, are required for the wiring materials, such as insulated wires, cables, cords, optical fiber cores, and optical fiber cords, used for internal or external wiring in electric and electronic devices.
[0003] In the wiring material as described above, in order to improve the characteristics, a crosslinking treatment is often performed on the resin or rubber forming the coating layer. The method of crosslinking the resin or rubber is generally an electron beam crosslinking method or a chemical crosslinking method. For example, methods of crosslinking polyolefin resin such as polyethylene include an electron beam crosslinking method in which crosslinking is performed by irradiating with an electron beam, a crosslinking method in which a crosslinking reaction is caused by applying heat after molding to the resin by the action of an organic peroxide, and a chemical crosslinking method such as a silane crosslinking method. Here, the silane crosslinking method is a method in which a silane coupling agent having an unsaturated group is subjected to a silane grafting reaction (also simply referred to as a grafting reaction) with a resin or rubber in the presence of an organic peroxide to obtain a silane grafted resin or rubber, and then the silane grafted resin or rubber is brought into contact with moisture in the presence of a silanol condensation catalyst to obtain a crosslinked resin. Among the above methods, the silane crosslinking method in particular does not require special equipment for the crosslinking treatment and can therefore be used in a wide range of fields.
[0004] On the other hand, wiring materials are sometimes used in conditions where they may come into contact with oil, and wiring materials used in such applications are required to have oil resistance (the property of keeping physical properties small even when immersed in oil).
[0005] As an example of a method for producing an oil-resistant molded article using the silane crosslinking method, for example, Patent Document 1 describes a production method in which a base resin containing specific amounts of acrylic rubber and polypropylene resin, an organic peroxide, a metal hydrate, a silane coupling agent, and a silanol condensation catalyst are melt-mixed, molded, and the resulting molded article is brought into contact with water. Patent Document 2 describes a production method in which a base rubber containing specific amounts of ethylene-acrylic rubber and polyolefin resin modified with an unsaturated carboxylic acid component, an organic peroxide, an inorganic filler, a silane coupling agent, and a silanol condensation catalyst are melt-mixed, molded, and the resulting molded article is brought into contact with water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-188307 A [Patent Document 2] JP 2019-116582 A Summary of the Invention [Problem to be solved by the invention]
[0007] The above-mentioned technology described in Patent Documents 1 and 2, which employs a base rubber containing a combination of acrylic rubber and a specific component in a specific silane crosslinking method, makes it possible to improve oil resistance. On the other hand, from the viewpoint of further increasing the productivity of industrial production, it is preferable that the manufacturing method of the wiring material can accommodate a wide range of manufacturing conditions. However, there is a problem that changes in manufacturing conditions naturally tend to affect product characteristics. For example, in the above-mentioned silane crosslinking method, when silane crosslinking is performed after extrusion molding to manufacture a small-sized molded body or a thin-walled molded body, the extrusion speed (linear speed) may be kept the same, but the screw rotation speed of the extruder may be reduced. In this case, the silane-grafted resin or rubber remains in the cylinder of the extruder for a long time, and silane crosslinking is likely to occur in some parts there due to the heat of the cylinder. As a result, there is a problem that gels or bumps are generated on the surface of the extrusion molded body, causing poor appearance. As a result of the inventors' investigations, it has become clear that the manufacturing methods described in Patent Documents 1 and 2 cannot adequately accommodate changes in the screw rotation speed of the resin or rubber (changes in the coating film thickness, etc.). Moreover, the molded body obtained by the manufacturing method described in Patent Document 2 is very hard and is unsuitable as a wiring material used in applications requiring flexibility. Furthermore, it has become clear that when oil is used to provide the wiring material with good appearance and flexibility, there is a problem in that the oil bleeds onto the wiring material surface.
[0008] An object of the present invention is to provide a production method by which a silane-crosslinked acrylic rubber molded article having excellent appearance, high-temperature oil resistance, mechanical properties, and flexibility and suppressed bleeding can be obtained, and to provide a silane-crosslinked acrylic rubber molded article and a silane-crosslinked acrylic rubber molded product obtained by this production method. Another object of the present invention is to provide a silane-crosslinkable acrylic rubber composition suitable for producing the silane-crosslinked acrylic rubber molded article. [Means for solving the problem]
[0009] The present inventors have found that, in the silane crosslinking method using ethylene-acrylic rubber, when a silane crosslinked acrylic rubber molded body is produced by using a base acrylic rubber in combination with a styrene elastomer and a mineral oil in a specific amount and ratio, the obtained silane crosslinked acrylic rubber molded body can be given an excellent level of appearance and flexibility while maintaining high-temperature oil resistance and mechanical properties, and bleeding can also be suppressed. Based on this finding, the present inventors have conducted further research and have come up with the present invention.
[0010] That is, the object of the present invention has been achieved by the following means. [1] A method for producing a silane-crosslinked acrylic rubber molded product, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.6 parts by mass of an organic peroxide, 1 to 200 parts by mass of an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base acrylic rubber in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of a base acrylic rubber, and grafting the grafting reaction site with the grafting reaction site of the base acrylic rubber by the radicals generated from the organic peroxide, thereby obtaining a silane crosslinkable acrylic rubber composition containing a silane crosslinkable acrylic rubber. Step (2): A step of molding the silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked acrylic rubber molded product. the base acrylic rubber contains 20 to 85% by mass of ethylene-acrylic rubber, 60% by mass or less of ethylene resin, 1 to 20% by mass of styrene elastomer, and 1 to 20% by mass of mineral oil, such that the ratio of the content of the styrene elastomer to the content of the mineral oil (content of styrene elastomer:content of mineral oil) is 1:2.5 to 1:0.5 by mass, In carrying out the step (1), A method for producing a silane-crosslinked acrylic rubber molded product, in which, when the entire base acrylic rubber is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), and (c), and, in which, when a part of the base acrylic rubber is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), (b), and (c). Step (a-1): A step of mixing the inorganic filler and the silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and all or a part of the base acrylic rubber in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and causing a graft reaction between the graft reaction site and a graft reaction-capable site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): Melt-mixing the remainder of the base acrylic rubber and the silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch with the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable acrylic rubber composition. [2] The ethylene resin has a viscosity of 0.910 to 0.940 g / cm 3 The method for producing a silane-crosslinked acrylic rubber molding according to [1], wherein the resin is an ethylene-α-olefin copolymer resin, an ethylene-vinyl acetate copolymer resin, or a mixture thereof having a density of 100% or more. [3] The method for producing a silane-crosslinked acrylic rubber molded product according to [1] or [2], wherein the base acrylic rubber contains 1 to 6 mass % of a propylene resin relative to 100 mass % of the base acrylic rubber. [4] The method for producing a silane-crosslinked acrylic rubber molded product according to any one of [1] to [3], wherein the inorganic filler is mixed in an amount of 30 to 200 parts by mass per 100 parts by mass of the base acrylic rubber. [5] The method for producing a silane-crosslinked acrylic rubber molded product according to any one of [1] to [4], wherein the silanol condensation catalyst is blended in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the base acrylic rubber. [6] The method for producing a silane-crosslinked acrylic rubber molded product according to any one of [1] to [5], wherein the ethylene-acrylic rubber comprises a binary copolymer of ethylene and an alkyl acrylate, or a ternary copolymer of ethylene, an alkyl acrylate, and a copolymerization component containing a carboxy group, or a mixture thereof. [7] The method for producing a silane-crosslinked acrylic rubber molded article according to any one of [1] to [6], wherein the inorganic filler is a metal hydrate. [8] The method for producing a silane-crosslinked acrylic rubber molded product according to any one of [1] to [7], wherein in the step (1), 30 to 180 parts by mass of the inorganic filler, 1 to 15 parts by mass of the silane coupling agent, 0.01 to 0.6 parts by mass of the organic peroxide, and 0.01 to 0.5 parts by mass of the silanol condensation catalyst are melt-mixed with respect to 100 parts by mass of the base acrylic rubber. [9] A silane-crosslinkable acrylic rubber composition produced by the step (1) of the production method according to any one of [1] to [8].
[10] A silane-crosslinked acrylic rubber molded article produced by the method for producing a silane-crosslinked acrylic rubber molded article according to any one of [1] to [8].
[11] A silane-crosslinked acrylic rubber molded article comprising the silane-crosslinked acrylic rubber molded article according to
[10] .
[0011] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. Effect of the Invention
[0012] The present invention provides a production method capable of obtaining a silane-crosslinked acrylic rubber molded article having excellent appearance, high-temperature oil resistance, mechanical properties, and flexibility and suppressed bleeding, a silane-crosslinked acrylic rubber molded article obtained by the production method, and a silane-crosslinked acrylic rubber molded article. Also, a silane-crosslinkable acrylic rubber composition suitable for producing a silane-crosslinked acrylic rubber molded article exhibiting such excellent properties can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] First, each component used in the present invention will be described.
[0014] <Base acrylic rubber> The base acrylic rubber used in the present invention contains ethylene-acrylic rubber, styrene elastomer, and paraffin oil as rubber components. The base acrylic rubber may further contain ethylene resin as an optional component. All of these components have a site capable of grafting reaction with the grafting reaction site of the silane coupling agent in the presence of radicals generated from an organic peroxide, such as an unsaturated bond site of a carbon chain or a carbon atom having a hydrogen atom in the main chain or at its terminal. The base acrylic rubber component may contain rubbers or resins other than ethylene-acrylic rubber, styrene elastomer, paraffin oil, and ethylene resin to the extent that the properties are not impaired. Such rubber or resin components are not particularly limited as long as they are polymeric resins or rubbers having a grafting reaction site of a silane coupling agent and a site capable of undergoing a grafting reaction in the presence of an organic peroxide, such as an unsaturated bond site on a carbon chain or a carbon atom having a hydrogen bond in the main chain or at its terminal.
[0015] - Ethylene-acrylic rubber - In the present invention, the ethylene-acrylic rubber refers to a rubber obtained by copolymerizing at least ethylene and an alkyl acrylate as constituent components. The ethylene-acrylic rubber preferably contains 50% by mass or more of an alkyl acrylate component. The alkyl acrylate component is preferably 60% by mass or less. The rubber more preferably contains methyl acrylate and / or ethyl acrylate as a monomer component, and particularly preferably contains methyl acrylate. As the ethylene-acrylic rubber, rubbers made of various copolymers such as a binary copolymer of ethylene and an alkyl acrylate ester, or a terpolymer obtained by further copolymerizing the binary copolymer with a copolymer component containing a carboxyl group can be particularly preferably used. Such copolymer components containing a carboxyl group include compounds having a carboxyl group and an unsaturated group (usually an ethylenic unsaturated group) copolymerizable with ethylene or an alkyl acrylate ester. For example, (meth)acrylic acid and maleic acid can be mentioned. As the terpolymer, for example, an ethylene-alkyl acrylate ester-acrylic acid copolymer or an ethylene-alkyl acrylate ester-maleic acid copolymer can be mentioned, and in particular, an ethylene-alkyl acrylate ester-acrylic acid copolymer is preferable. The ethylene-acrylic rubber may be used alone or in combination of two or more kinds. Examples of ethylene-acrylic rubbers made of binary copolymers include Baymac DP and Baymac DLS. Examples of ethylene-acrylic rubbers made of ternary copolymers include Baymac G, Baymac HG, Baymac LS, Baymac GLS, and Baymac Ultra HT-OR (trade names, all manufactured by DuPont-Mitsui Polychemicals).
[0016] - Ethylene resin - By incorporating an ethylene resin in the base acrylic rubber of the present invention, the mechanical properties can be improved. The ethylene resin is not particularly limited as long as it is a resin (excluding PP resin) made of a polymer obtained by polymerizing or copolymerizing a compound having an ethylenically unsaturated bond, and those conventionally used for the application of electric wire covering materials can be used. For example, resins made of various polymers such as polyethylene, ethylene-α-olefin copolymer, polyolefin copolymer having an acid copolymerization component or an acid ester copolymerization component can be mentioned. Among them, polyethylene resin, and polyolefin copolymer resin having an acid copolymerization component or an acid ester copolymerization component are preferred. The polyethylene resin may be any resin of a polymer containing an ethylene component, and includes a homopolymer consisting of ethylene alone, a copolymer of ethylene and an α-olefin (preferably 5 mol% or less) (excluding those corresponding to polypropylene), and a copolymer of ethylene and a non-olefin (preferably 1 mol% or less) having only carbon, oxygen and hydrogen atoms in the functional group. The above-mentioned α-olefin and non-olefin may be any known one that has been conventionally used as a copolymerization component of polyethylene, without any particular limitation. Examples of polyethylene resins include LDPE (low density polyethylene), LLDPE (linear low density polyethylene), and MDPE (medium density polyethylene). LLDPE may be LLDPE (linear low density polyethylene) synthesized in the presence of a metallocene catalyst. These polyethylene resins may be used alone or in combination of two or more. Among these polyethylene resins, it is preferable to use LLDPE. Examples of the ethylene-α-olefin copolymer resin include copolymer resins of ethylene and an α-olefin having 4 to 12 carbon atoms, and examples of the α-olefin include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, etc. These ethylene-α-olefin copolymer resins may be used alone or in combination of two or more. The acid copolymerization component or acid ester copolymerization component in the polyolefin copolymer resin having an acid copolymerization component or an acid ester copolymerization component is not particularly limited, and examples thereof include carboxylic acid compounds such as (meth)acrylic acid, and acid ester compounds such as vinyl acetate or alkyl (meth)acrylate (preferably having an alkyl group having 1 to 12 carbon atoms). Examples of the polyolefin copolymer resin having an acid copolymerization component or an acid ester copolymerization component include resins such as ethylene-vinyl acetate copolymer (EVA), ethylene-(meth)acrylic acid copolymer, and ethylene-alkyl (meth)acrylate copolymer (preferably ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-butyl acrylate copolymer). The ethylene resin is preferably an ethylene-α-olefin copolymer resin, an ethylene-vinyl acetate copolymer resin, or a mixture thereof. Incidentally, examples of commercially available polyethylene resins and ethylene-α-olefin copolymer resins that can be used for the base acrylic rubber according to the present invention include "Evolue" (product name: manufactured by Prime Polymer Co., Ltd.).
[0017] The density of ethylene-α-olefin copolymer resin is 0.910 to 0.940 g / cm 3 is preferable, and 0.920 to 0.940 g / cm 3 is more preferable. This further increases the inorganic filler acceptance, and excellent mechanical properties can be obtained while maintaining high temperature oil resistance. The density of the ethylene-α-olefin copolymer resin can be measured by the method described in JIS K 7112.
[0018] Ethylene resin is 0.910 to 0.940 g / cm 3 Preferably, the resin is an ethylene-α-olefin copolymer resin having a density of 100 to 2000 nm, an ethylene-vinyl acetate copolymer resin having a density of 100 to 2000 nm, or a mixture thereof.
[0019] The ethylene resin may be modified with an acid. The acid used for the modification is not particularly limited, and examples thereof include commonly used unsaturated carboxylic acids.
[0020] - Styrene elastomer - The styrene elastomer used in the present invention is a copolymer block of components derived from an aromatic vinyl compound and a conjugated diene compound, and / or a hydrogenated product of a block copolymer or random copolymer mainly composed of components derived from the above compounds. The aromatic vinyl compound may be one or more selected from, for example, styrene, α-methylstyrene, vinyltoluene, p-tertiary butylstyrene, etc., with styrene being preferred among them. The conjugated diene compound may be one or more selected from, for example, butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, etc., with butadiene, isoprene, or a combination thereof being preferred among them. As the styrene elastomer, a binary or ternary copolymer composed of a polystyrene block and an elastomer block having a polyolefin structure can be used. The hydrogenated copolymer (hereinafter sometimes referred to as hydrogenated copolymer) preferably contains 5 to 70 mass %, more preferably 10 to 60 mass %, of a component derived from an aromatic vinyl compound. This content can be determined, for example, by measuring the UV absorption spectrum with a UV spectrophotometer using a chloroform solution. Examples of styrene elastomers include SBS (styrene-butadiene-styrene block copolymer), SIS (styrene-isoprene-styrene block copolymer), SEBS (styrene-ethylene-butylene-styrene block copolymer: hydrogenated SBS), SEEPS (styrene-ethylene-ethylene-propylene-styrene block copolymer), SEPS (styrene-ethylene-propylene-styrene block copolymer: hydrogenated SIS), HSBR (hydrogenated styrene-butadiene random copolymer), etc. The styrene elastomer may be one type or two or more types. Examples of styrene elastomers include "Septon" (product name, manufactured by Kuraray Co., Ltd.), "Tuftec" (product name, manufactured by Asahi Kasei Chemicals Corporation), and "Dynaron" (product name, manufactured by JSR Corporation).
[0021] - Mineral oil - The mineral oil used in the present invention is a mixed oil containing an oil having an aromatic ring, an oil having a naphthene ring, and an oil having a paraffin chain. Paraffin oil refers to an oil in which the carbon number (CP) of the paraffin chain is, for example, 50% or more and less than 75% of the total carbon number of the aromatic ring, naphthene ring, and paraffin chain, the carbon number (CN) of the naphthene chain is 20 or more and less than 40%, and the carbon number of the aromatic ring (CA) is 3 or more and less than 10%. Naphthene oil refers to an oil in which CN is 40 or more and less than 60%, CP is 30% or more and less than 50%, and CA is 8% or more and less than 16% of the total carbon number, and aromatic oil refers to an oil in which CA is 16% or more. As the mineral oil (rubber softener), paraffin oil or naphthene oil can be used, with paraffin oil being preferred in terms of mechanical strength. The paraffin oil preferably has a dynamic viscosity at 40°C of 20 to 500 cSt, a pour point of -10 to -15°C, and a flash point (COC) of 180 to 300°C. Examples of mineral oils include "Diana Process Oil" (trade name, manufactured by Idemitsu Kosan Co., Ltd.) and "Cosmo Neutral" (trade name, manufactured by Cosmo Oil Lubricants Co., Ltd.).
[0022] - Other base acrylic rubber components - Propylene resin and the like can be used as long as the effects of the present invention are not impaired.
[0023] The propylene resin may be any resin whose main component is a polymer containing a propylene constituent, and resins such as a propylene homopolymer, an ethylene-propylene random copolymer, or an ethylene-propylene block copolymer can be used. The ethylene-propylene random copolymer refers to a copolymer having an ethylene content of about 1 to 10% by mass, in which the ethylene component is randomly incorporated into the propylene chain. The ethylene-propylene block copolymer refers to a copolymer having an ethylene or ethylene-propylene rubber (EPR) content of about 5 to 20% by mass, in which the ethylene or EPR component is present independently in the propylene component in an island-sea structure. In terms of appearance, the propylene resin is particularly preferably an ethylene-propylene random copolymer resin. The ethylene content is a value measured in accordance with the method described in ASTM D3900. The propylene resin may be used alone or in combination of two or more kinds.
[0024] - Content in base acrylic rubber - The base acrylic rubber contains 20 to 85 mass% ethylene-acrylic rubber, 60 mass% or less ethylene resin, 1 to 20 mass% styrene elastomer, and 1 to 20 mass% mineral oil, such that the ratio of the styrene elastomer content to the mineral oil content (styrene elastomer content:mineral oil content) is 1:2.5 to 1:0.5 by mass. The content of each component in the base acrylic rubber is preferably determined within the following ranges so that the total of each component is 100 mass %.
[0025] The content of the ethylene-acrylic rubber is 20 to 85% by mass in 100% by mass of the base acrylic rubber. If this content is too low, the heat-resistant silane-crosslinked acrylic rubber molding may not be able to have sufficient high-temperature oil resistance and flexibility. On the other hand, if the content is too high, the heat-resistant silane-crosslinked resin molding may not be able to have sufficient mechanical strength (tensile strength). In addition, the heat-resistant silane-crosslinked resin molding may tack and fuse to each other. The content of the ethylene-acrylic rubber in the base acrylic rubber is preferably 30 to 85% by mass. When the content of the ethylene-acrylic rubber is within the above range, the high-temperature oil resistance and flexibility of the heat-resistant silane-crosslinked resin molded article can be further improved.
[0026] From the viewpoint of improving flexibility and high-temperature oil resistance, the content of the ethylene resin is 60% by mass or less, preferably 5 to 50% by mass, and more preferably 15 to 40% by mass, in 100% by mass of the base acrylic rubber.
[0027] The content of the styrene elastomer is 1 to 20 mass%, preferably 1 to 10 mass%, and more preferably 2 to 8 mass%, in 100 mass% of the base acrylic rubber. Within this range, high-temperature oil resistance and mechanical properties can be improved, and excellent appearance can be imparted.
[0028] The content of the mineral oil is 1 to 20 mass%, preferably 1 to 10 mass%, and more preferably 2 to 8 mass%, in 100 mass% of the base acrylic rubber. Within this range, high-temperature oil resistance and mechanical properties can be improved, and excellent appearance can be imparted.
[0029] The ratio of the styrene elastomer content to the mineral oil content (styrene elastomer content:mineral oil content) is 1:2.5 to 1:0.5 by mass, and more preferably 1:2 to 1:0.8. When it is in this range, bleeding can be suppressed while imparting high temperature oil resistance.
[0030] When the base acrylic rubber contains other base acrylic rubber components, the content of the other base acrylic rubber components is not particularly limited as long as the amounts of the ethylene-acrylic rubber, ethylene resin, styrene elastomer, and mineral oil are within the above-mentioned ranges; however, the content is preferably 40 to 75 mass%, and more preferably 50 to 70 mass%, of 100 mass% of the base acrylic rubber. When the other base acrylic rubber component is a propylene resin, the content of the propylene resin in 100% by mass of the base acrylic rubber is preferably 1 to 6% by mass, and more preferably 1 to 5% by mass.
[0031] <Organic peroxide> The organic peroxide generates radicals at least by thermal decomposition, and acts as a catalyst to initiate a grafting reaction of the silane coupling agent to the rubber component by radical reaction (a covalent bond forming reaction between the grafting reaction site of the silane coupling agent and the grafting reaction site of the rubber component, also called a (radical) addition reaction). In particular, when the silane coupling agent contains an ethylenically unsaturated group as the grafting reaction site, the organic peroxide acts to initiate a grafting reaction by radical reaction between the ethylenically unsaturated group and the rubber component (including a reaction of abstracting hydrogen radicals from the rubber component). The organic peroxide is not particularly limited as long as it generates radicals. For example, an organic peroxide represented by the general formula: 1 -O-O-R 2 , R 3 -OO-C(=O)R 4 , R 5 C(=O)-OO(C=O)R 6 Preferred are compounds represented by the formula: 1 ~R 6 Each independently represents an alkyl group, an aryl group, or an acyl group. R 1 ~R 6 Among these, it is preferable that all of them are alkyl groups, or that one of them is an alkyl group and the remaining is an acyl group.
[0032] Examples of such organic peroxides include those described in paragraph
[0037] of International Publication No. 2015 / 046478, the contents of which are incorporated herein by reference as part of the present specification. In terms of odor, coloring, and scorch stability, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3 are preferred.
[0033] The decomposition temperature of the organic peroxide is preferably 120 to 195° C., particularly preferably 125 to 180° C. The decomposition temperature of the organic peroxide is equal to or lower than the melt mixing temperature in the step (a-2) described below. In the present invention, the decomposition temperature of an organic peroxide means the temperature at which a single-component organic peroxide undergoes a decomposition reaction into two or more compounds when heated at a certain temperature or temperature range. Specifically, it means the temperature at which heat absorption or heat generation begins when heated from room temperature at a temperature increase rate of 5°C / min in a nitrogen gas atmosphere by thermal analysis such as DSC method.
[0034] <Inorganic filler> In the present invention, the inorganic filler can be used without any particular limitation as long as it has a site on its surface that can be chemically bonded to the reactive site of the silanol group of the silane coupling agent by hydrogen bond, covalent bond, or intermolecular bond. Examples of the site in the inorganic filler that can be chemically bonded to the reactive site of the silane coupling agent include OH groups (hydroxyl groups, water molecules of water of water or crystallization, OH groups such as carboxyl groups), amino groups, and SH groups.
[0035] The inorganic filler is not particularly limited, and examples thereof include metal hydrates such as compounds having hydroxyl groups or crystal water, such as aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, hydrated aluminum silicate, hydrated magnesium silicate, basic magnesium carbonate, hydrotalcite, and talc. Other examples include boron nitride, silica (crystalline silica, amorphous silica, etc.), carbon, clay, zinc oxide, tin oxide, titanium oxide, molybdenum oxide, antimony trioxide, silicone compounds, quartz, zinc borate, white carbon, zinc borate, zinc hydroxystannate, and zinc stannate. One type of inorganic filler may be used alone, or two or more types may be used in combination. The inorganic filler is preferably at least one selected from metal hydrates (more preferably aluminum hydroxide, magnesium hydroxide), silica, clay, talc, calcium carbonate, and the like, and more preferably metal hydrates.
[0036] The inorganic filler may be a surface-treated inorganic filler that has been surface-treated with a silane coupling agent or the like. For example, examples of the silane coupling agent surface-treated inorganic filler include Kisuma 5L and Kisuma 5P (both trade names, magnesium hydroxide, manufactured by Kyowa Chemical Industry Co., Ltd.). The amount of the silane coupling agent used to treat the surface of the inorganic filler is not particularly limited, but is, for example, 3 mass% or less.
[0037] The average particle size of the inorganic filler is preferably 0.2 to 10 μm, more preferably 0.3 to 8 μm, further preferably 0.4 to 5 μm, and particularly preferably 0.4 to 3 μm. The average particle size is determined by dispersing the inorganic filler in alcohol or water and using an optical particle size measuring device such as a laser diffraction / scattering type particle size distribution measuring device.
[0038] <Silane coupling agent> The silane coupling agent used in the present invention has a grafting reaction site (group or atom) that can undergo a grafting reaction with the base acrylic rubber in the presence of radicals generated by decomposition of the organic peroxide. It also has a reaction site (including a site generated by hydrolysis, such as a silyl ester group) that can react with a site that can chemically bond with the inorganic filler and undergo silanol condensation. Examples of such silane coupling agents include silane coupling agents that have been used in the silane crosslinking method. As the silane coupling agent, for example, a compound represented by the following general formula (1) can be used.
[0039] [ka]
[0040] In general formula (1), R a11 is a group containing an ethylenically unsaturated group, R b11 is an aliphatic hydrocarbon group, a hydrogen atom or Y 13 Y 11 , Y 12 and Y 13 is a hydrolyzable organic group. Y 11 , Y 12and Y 13 may be the same or different from each other.
[0041] R a11 is a grafting reaction site, and is preferably a group containing an ethylenically unsaturated group. Examples of the group containing an ethylenically unsaturated group include a vinyl group, a (meth)acryloyloxyalkylene group, and a p-styryl group. Among these, a vinyl group is preferred. R b11 represents an aliphatic hydrocarbon group, a hydrogen atom, or Y 13 The aliphatic hydrocarbon group includes a monovalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, excluding aliphatic unsaturated hydrocarbon groups. R b11 is preferably Y 13 It is.
[0042] Y 11 , Y 12 and Y 13 indicates a reactive site capable of silanol condensation (hydrolyzable organic group). Examples include an alkoxy group having 1 to 6 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, and an acyloxy group having 1 to 4 carbon atoms, with an alkoxy group being preferred. Specific examples of the hydrolyzable organic group include methoxy, ethoxy, butoxy, and acyloxy. Among these, methoxy or ethoxy is more preferred from the viewpoint of the reactivity of the silane coupling agent.
[0043] The silane coupling agent is preferably a silane coupling agent having a fast hydrolysis rate, and more preferably R b11 Y 13 and Y 11 , Y 12 and Y 13 or Y 11 , Y 12 and Y 13 At least one of the groups is a methoxy group.
[0044] Specific examples of the silane coupling agent include vinyl alkoxysilanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tributoxy silane, vinyl dimethoxy ethoxy silane, vinyl dimethoxy butoxy silane, vinyl diethoxy butoxy silane, allyl trimethoxy silane, allyl triethoxy silane, and vinyl triacetoxy silane; and (meth)acryloxy alkoxy silanes such as methacryloxy propyl trimethoxy silane, methacryloxy propyl triethoxy silane, and methacryloxy propyl methyl dimethoxy silane.
[0045] Among the above silane coupling agents, silane coupling agents having a vinyl group and an alkoxy group at the terminal are more preferred, and vinyltrimethoxysilane or vinyltriethoxysilane is particularly preferred.
[0046] The silane coupling agent may be used alone or in combination of two or more kinds. In addition, the silane coupling agent may be used as it is or after diluting with a solvent or the like.
[0047] <Silanol condensation catalyst> The silanol condensation catalyst acts to cause a condensation reaction of the silane coupling agent grafted to the base acrylic rubber in the presence of moisture. Based on the action of this silanol condensation catalyst, the rubber components are crosslinked with each other via the silane coupling agent. As a result, a silane-crosslinked acrylic rubber molded product having excellent tensile strength is obtained. In addition, if necessary, a silane-crosslinked acrylic rubber molded product having excellent heat resistance can also be obtained.
[0048] The silanol condensation catalyst is not particularly limited, and examples thereof include organic tin compounds, metal soaps, platinum compounds, etc. Examples of common silanol condensation catalysts include dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctiate, dibutyltin diacetate, zinc stearate, lead stearate, barium stearate, calcium stearate, sodium stearate, lead naphthenate, lead sulfate, zinc sulfate, organic platinum compounds, etc. The silanol condensation catalyst may be used alone or in combination of two or more.
[0049] <Career> The silanol condensation catalyst is mixed with a resin or rubber as desired and used. Such resin or rubber (also called a carrier) is not particularly limited, but the rubber and / or resin components described in the base acrylic rubber can be used. Ethylene-acrylic rubber and ethylene resin are preferred, and LLDPE and EVA are more preferred.
[0050] <Additives> In the present invention, various additives that are generally used in electric wires, electric cables, electric cords, automotive parts, office automation equipment, building parts, miscellaneous goods, sheets, foams, tubes, pipes, etc. may be appropriately blended within a range that does not impair the intended effects. Examples of such additives include crosslinking assistants, antioxidants, lubricants, metal deactivators, flame retardants (assistants), other resins, etc.
[0051] The crosslinking aid is a compound that forms a partially crosslinked structure with the rubber component in the presence of an organic peroxide, and examples of such compounds include polyfunctional compounds. The antioxidant is not particularly limited, but examples thereof include amine antioxidants, phenol antioxidants, and sulfur antioxidants. Examples of the lubricant include hydrocarbons, siloxanes, fatty acids, fatty acid amides, esters, alcohols, and metal soaps. Flame retardants include, but are not limited to, red phosphorus.
[0052] <Method of manufacturing silane-crosslinked acrylic rubber molded body> The method for producing the silane-crosslinked acrylic rubber molded article of the present invention will now be described in detail. The method for producing a silane-crosslinked acrylic rubber molded article of the present invention includes the following steps (1), (2), and (3). The silane-crosslinkable acrylic rubber composition of the present invention is produced by the following step (1).
[0053] Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, 1 to 200 parts by mass of an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base acrylic rubber in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of a base acrylic rubber, and grafting the grafting reaction site with the grafting reaction site of the base acrylic rubber by the radicals generated from the organic peroxide, thereby obtaining a silane crosslinkable acrylic rubber composition (reaction composition) containing a silane crosslinkable acrylic rubber. Step (2): A step of molding the silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked acrylic rubber molded product.
[0054] The above step (1) includes the following steps depending on the use mode of the base acrylic rubber. When the entire base acrylic rubber is melt-mixed in the below-described step (a-2), the step (1) has the below-described steps (a-1), (a-2), and (c), and when a portion of the base acrylic rubber is melt-mixed in the below-described step (a-2), the step (1) has the below-described steps (a-1), (a-2), (b), and (c). Step (a-1): A step of mixing an inorganic filler and a silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and all or a part of the base acrylic rubber in the presence of an organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause a graft reaction between the graft reaction site and the graft reaction site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): Melt-mixing the remainder of the base acrylic rubber and the silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch with a silanol condensation catalyst or catalyst master batch to obtain a silane-crosslinkable acrylic rubber composition. Hereinafter, both steps (a-1) and (a-2) may be collectively referred to as step (a).
[0055] In the manufacturing method of the present invention, the "base acrylic rubber" is a rubber for forming a silane-crosslinked acrylic rubber molded product or a silane-crosslinkable acrylic rubber composition. Therefore, in the manufacturing method of the present invention, it is sufficient that the reaction composition obtained in step (1) contains 100 parts by mass of the base acrylic rubber. For example, in step (a-2), the method includes "an embodiment in which the entire amount (100 parts by mass) of the base acrylic rubber is blended" and "an embodiment in which only a portion of the base acrylic rubber is blended."
[0056] When a portion of the base acrylic rubber is blended in step (a-2), 100 parts by mass of the base acrylic rubber blended in step (1) is the total amount of the base acrylic rubber mixed in step (a-2) and step (b). When the remainder of the base acrylic rubber is blended in step (b), preferably 80 to 95 mass %, more preferably 85 to 92 mass %, of the base acrylic rubber is blended in step (a-2), and preferably 5 to 20 mass %, more preferably 8 to 15 mass %, of the base acrylic rubber is blended in step (b).
[0057] In the step (1), the blending amounts (contents) of the ethylene-acrylic rubber, ethylene resin, styrene elastomer, mineral oil, etc. in the base acrylic rubber are as described above. The ratio of the styrene elastomer content to the mineral oil content is also as described above. The styrene elastomer and the mineral oil may be mixed in either step (a-2) or step (b), but are preferably mixed in step (a-2).
[0058] In step (1), the amount of the organic peroxide is 0.01 to 0.6 parts by mass, preferably 0.01 to 0.5 parts by mass, and more preferably 0.05 to 0.2 parts by mass, relative to 100 parts by mass of the base acrylic rubber. By making the amount of the organic peroxide 0.01 to 0.6 parts by mass, the grafting reaction can be carried out in an appropriate range, condensation between silane coupling agents can be suppressed, mechanical properties, and in some cases heat resistance and reinforcement properties can be sufficiently obtained, and direct crosslinking of the rubber component due to a side reaction can be suppressed, so that a composition with excellent appearance can be obtained without generating gel particles.
[0059] In step (1), the amount of inorganic filler is 1 to 200 parts by mass, preferably 30 to 200 parts by mass, more preferably 40 to 200 parts by mass, and even more preferably 30 to 180 parts by mass, relative to 100 parts by mass of the base acrylic rubber. By setting the amount of inorganic filler to 1 to 200 parts by mass, flexibility and mechanical properties required for wiring materials can be imparted to the silane-crosslinked acrylic rubber molded body. Furthermore, an increase in load during molding or kneading can be suppressed, making secondary molding possible.
[0060] In the step (1), the amount of the silane coupling agent is 1 to 15 parts by mass, preferably 1.5 to 7 parts by mass, and more preferably 2 to 5 parts by mass, based on 100 parts by mass of the base acrylic rubber. When the amount of the silane coupling agent is 1 to 15 parts by mass, the silane coupling agent is adsorbed on the surface of the inorganic filler, and the silane coupling agent is prevented from volatilizing during kneading, which is economical. In addition, the silane coupling agent that is not adsorbed is prevented from condensing, causing roughness such as gel particles on the molded body, which deteriorates the appearance. Furthermore, if necessary, the crosslinking reaction can be sufficiently advanced to exhibit excellent tensile strength. When the blending amount of the silane coupling agent is more than 2.0 parts by mass and not more than 15.0 parts by mass, a silane-crosslinked acrylic rubber molded article having even better high-temperature oil resistance can be produced.
[0061] In step (1), the amount of the silanol condensation catalyst is not particularly limited, and is preferably 0.01 to 0.5 parts by mass, more preferably 0.02 to 0.5 parts by mass, even more preferably 0.05 to 0.4 parts by mass, and particularly preferably 0.08 to 0.3 parts by mass, relative to 100 parts by mass of the base acrylic rubber. When the amount of the silanol condensation catalyst is within the above range, the generation of gel particles during molding can be suppressed, and crosslinking can be sufficiently advanced to provide excellent mechanical strength. In addition, heat resistance can be imparted as necessary.
[0062] From the viewpoint of imparting superior levels of appearance, high-temperature oil resistance, mechanical properties, and flexibility while suppressing bleeding, it is preferred in step (1) to melt-mix 30 to 180 parts by mass of an inorganic filler, 1 to 15 parts by mass of a silane coupling agent, 0.01 to 0.6 part by mass of an organic peroxide, and 0.01 to 0.5 part by mass of a silanol condensation catalyst with respect to 100 parts by mass of the base acrylic rubber.
[0063] In carrying out step (1), steps (a-1) and (a-2) are carried out in sequence. That is, first, the inorganic filler and the silane coupling agent are mixed, and then the obtained mixture and all or a part of the base acrylic rubber are melt-kneaded in the above-mentioned blending amounts at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause the above-mentioned grafting reaction to occur, thereby preparing a silane master batch. The method for mixing the base acrylic rubber is not particularly limited. For example, a base acrylic rubber that has been mixed and prepared in advance may be used, or each component, for example, each rubber component, may be mixed separately.
[0064] In the present invention, the silane coupling agent is not introduced alone into the silane master batch, but is premixed with the inorganic filler. That is, the inorganic filler and the silane coupling agent are mixed to prepare a mixture (step (a-1)). The premixed silane coupling agent is present so as to surround the surface of the inorganic filler, and it is considered that a part or all of it is adsorbed or bonded to the inorganic filler. This can reduce the volatilization of the silane coupling agent during the subsequent melt mixing. In addition, it can also prevent the silane coupling agent that is not adsorbed or bonded to the inorganic filler from condensing, making melt kneading difficult. Furthermore, it is also possible to obtain a desired shape during extrusion molding.
[0065] The method of premixing the inorganic filler and the silane coupling agent is not particularly limited, but includes mixing methods such as wet processing and dry processing. Specifically, the inorganic filler and the silane coupling agent are mixed by dry or wet processing for several minutes to several hours at a temperature below the decomposition temperature of the organic peroxide, preferably 10 to 60°C, more preferably around room temperature (20 to 25°C), and a dry processing in which the silane coupling agent is added to the inorganic filler, preferably the dried inorganic filler, with or without heating and mixed is more preferred. In step (a-1), the base acrylic rubber may be mixed as long as the temperature is maintained below the decomposition temperature.
[0066] In the manufacturing method of the present invention, the mixture of inorganic filler and silane coupling agent obtained in step (a-1) is then melt-mixed with all or a part of the base acrylic rubber in the presence of an organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide (step (a-2)). In this way, excessive crosslinking reaction between the base acrylic rubber components can be prevented, and a crosslinked molded product with excellent appearance can be obtained. In the melt mixing step (a-2), the radicals generated from the organic peroxide cause a graft reaction between the graft reaction site of the silane coupling agent and the graft reaction site of the base acrylic rubber. As a result, a silane crosslinkable acrylic rubber (silane graft polymer) in which the silane coupling agent is covalently bonded to the rubber component is synthesized, and a silane master batch containing this silane crosslinkable acrylic rubber is prepared.
[0067] In step (a-2), the temperature at which the above components are melt-mixed (also referred to as melt-kneading or kneading) is equal to or higher than the decomposition temperature of the organic peroxide, preferably a temperature of the decomposition temperature of the organic peroxide + (25 to 110) ° C, more preferably 150 to 230 ° C. The decomposition temperature of the organic peroxide is preferably set after the base acrylic rubber component is melted. At the above mixing temperature, the above components melt, the organic peroxide decomposes and acts, and the necessary silane grafting reaction proceeds sufficiently in step (a-2). The mixing time may be a time at which the reaction mixture is sufficiently mixed and the silane grafting reaction can be completed, and is appropriately set between 3 and 20 minutes, but is not limited thereto. Other conditions can be appropriately set. The mixing method is not particularly limited as long as it is a method normally used for rubber, plastics, etc. As the kneading device, a single screw extruder, a twin screw extruder, a roll, a Banbury mixer, various kneaders, etc. are used. In terms of the dispersibility of the base acrylic rubber component and the stability of the crosslinking reaction, a closed type mixer such as a Banbury mixer or various kneaders is preferred.
[0068] The organic peroxide may be present during the melt mixing in the above step (a-2), i.e., when the mixture obtained in step (a-1) is melt mixed with the base rubber. The organic peroxide may be mixed, for example, in step (a-1) or in step (a-2). The organic peroxide is preferably mixed in step (a-1).
[0069] In steps (a-1) and (a-2), especially in step (a-2), it is preferable to knead the above-mentioned components substantially without mixing a silanol condensation catalyst. This can suppress the condensation reaction of the silane coupling agent, facilitate melt mixing, and allow the desired shape to be obtained during extrusion molding. Here, "substantially without mixing" does not mean to exclude the silanol condensation catalyst that is inevitably present, but means that it may be present to the extent that the above-mentioned problems due to silanol condensation of the silane coupling agent do not occur. For example, in step (a-2), the silanol condensation catalyst may be present in an amount of 0.01 parts by mass or less relative to 100 parts by mass of the base acrylic rubber.
[0070] In this way, the step (a) consisting of the steps (a-1) and (a-2) is carried out to graft the silane coupling agent with the base acrylic rubber to prepare a silane master batch (also called silane MB). The silane MB thus obtained is used, as described later, preferably together with a silanol condensation catalyst or a catalyst master batch described later in the manufacture of the reaction composition (silane crosslinkable acrylic rubber composition) prepared in the step (1). The silane MB is a mixture containing a silane crosslinkable acrylic rubber in which the silane coupling agent has been grafted to the rubber component to such an extent that it can be molded in the step (2) described later.
[0071] In the manufacturing method of the present invention, when a part of the base acrylic rubber is melt-mixed in step (a-2), the rest of the base acrylic rubber is melt-mixed with a silanol condensation catalyst to prepare a catalyst master batch (also called catalyst MB) in step (b). Therefore, when the whole of the base acrylic rubber is melt-mixed in step (a-2), step (b) does not need to be performed, and other base acrylic rubber components may be mixed with the silanol condensation catalyst.
[0072] The mixing ratio of the base acrylic rubber as the carrier and the silanol condensation catalyst is not particularly limited, but is preferably set so as to satisfy the above-mentioned blending amounts in step (1). The mixing may be performed by any method that can achieve uniform mixing, including mixing performed under molten base acrylic rubber (melt mixing). Melt mixing can be performed in the same manner as in the melt mixing in the above step (a-2). For example, the mixing temperature can be appropriately set to a temperature equal to or higher than the melting temperature of the base acrylic rubber component, and is preferably 120 to 200°C, more preferably 140 to 180°C. Other conditions, such as the mixing time, can be appropriately set.
[0073] In step (b), other resins can be used as carriers instead of or in addition to the remainder of the base acrylic rubber. That is, in step (b), the remainder of the base acrylic rubber when a part of the base acrylic rubber is melt-mixed in step (a-2), or a resin other than the rubber component used in step (a-2), can be melt-mixed with a silanol condensation catalyst to prepare a catalyst master batch. When the carrier is another resin, the amount of the other resin is preferably 1 to 60 parts by mass, more preferably 2 to 50 parts by mass, and even more preferably 3 to 40 parts by mass, relative to 100 parts by mass of the base acrylic rubber, in order to promote the grafting reaction in step (a-2) and to prevent the formation of bumps during molding.
[0074] In addition, an inorganic filler may be used in step (b). In this case, the amount of the inorganic filler in step (b) is not particularly limited, but is preferably 350 parts by mass or less per 100 parts by mass of the carrier. By setting the amount of the inorganic filler to 350 parts by mass or less, the silanol condensation catalyst is appropriately dispersed, and crosslinking is likely to proceed.
[0075] The catalyst MB thus prepared is a (molten) mixture of the silanol condensation catalyst and the carrier, with or without a filler. This catalyst MB is used together with the silane MB in the production of the silane-crosslinkable acrylic rubber composition prepared in step (1).
[0076] In the manufacturing method of the present invention, the next step is to melt-mix the silane MB and the silanol condensation catalyst or catalyst MB to obtain a silane-crosslinkable acrylic rubber composition (reaction composition). This reaction composition is a composition containing the silane-crosslinkable acrylic rubber synthesized in the above step (a-2). The mixing method may be any method capable of obtaining a homogeneous reaction composition as described above.
[0077] The mixing is basically the same as the melt mixing in step (a-2). Although there are rubber components, such as elastomers, whose melting points cannot be measured by DSC or the like, the kneading is performed at a temperature at which at least the rubber components melt. The melt mixing temperature is appropriately selected according to the melting temperature of the base acrylic rubber or the carrier, and is, for example, preferably 80 to 250°C, more preferably 100 to 240°C. Other conditions, such as the mixing (kneading) time, can be appropriately set.
[0078] In step (c), in order to avoid silanol condensation reactions, it is preferable that the mixture of silane MB and silanol condensation catalyst is not kept at high temperature for a long period of time.
[0079] This step (c) may be any step in which the silane master batch is mixed with a silanol condensation catalyst or a catalyst master batch to obtain the above-mentioned reaction composition as a molten mixture thereof, and is preferably a step in which a catalyst master batch containing a silanol condensation catalyst and a carrier is melt-mixed with the silane master batch.
[0080] In this way, steps (a) to (c) (step (1)) are carried out to produce a silane crosslinkable acrylic rubber composition as a reaction composition. This silane crosslinkable acrylic rubber composition contains a base acrylic rubber containing 20 to 85 mass% of ethylene-acrylic rubber, 60 mass% or less of ethylene resin, 1 to 20 mass% of styrene elastomer, and 1 to 20 mass% of mineral oil, with the ratio of the content of the styrene elastomer to the content of the mineral oil (content of the styrene elastomer:content of the mineral oil) being 1:2.5 to 1:0.5 by mass, a silane crosslinkable acrylic rubber grafted with a silane coupling agent, 1 to 200 mass parts of an inorganic filler and a silanol condensation catalyst relative to 100 mass parts of the base acrylic rubber. This silane crosslinkable acrylic rubber composition contains silane crosslinkable acrylic rubbers with different crosslinking methods. In this silane crosslinkable acrylic rubber, the reactive site of the silane coupling agent capable of silanol condensation may be bonded or adsorbed to an inorganic filler, but is not silanol condensed as described below. Therefore, the silane crosslinkable acrylic rubber contains at least a crosslinkable rubber in which a silane coupling agent bonded or adsorbed to an inorganic filler is grafted to a base acrylic rubber, and a crosslinkable rubber in which a silane coupling agent not bonded or adsorbed to an inorganic filler is grafted to a base acrylic rubber. In addition, the silane crosslinkable acrylic rubber may have a silane coupling agent bonded or adsorbed to an inorganic filler, and a silane coupling agent not bonded or adsorbed to an inorganic filler. Furthermore, it may contain a rubber component that has not reacted with the silane coupling agent. As described above, the silane crosslinkable acrylic rubber is an uncrosslinked body in which the silane coupling agent is not condensed with silanol. In practice, when the silane coupling agent is melt-mixed in step (c), partial crosslinking is unavoidable, but the obtained silane crosslinkable acrylic rubber composition is one that maintains at least the moldability in the molding in step (2).
[0081] In step (1), steps (a) to (c) can be carried out simultaneously or consecutively.
[0082] In step (1), the amounts of other base acrylic rubber components that can be used in addition to the above components and the above additives are appropriately set within ranges that do not impair the object of the present invention. In step (1), the additives, particularly the antioxidant and the flame retardant, may be mixed in any step or component, but are preferably mixed in the carrier. In step (1), particularly in steps (a-1) and (a-2), it is preferable that the crosslinking aid is not substantially mixed. If the crosslinking aid is not substantially mixed, crosslinking between the rubber components during melt mixing is unlikely to occur, and the appearance of the silane-crosslinked acrylic rubber molded product is excellent. Here, "not substantially mixed" means that the crosslinking aid is not actively mixed, and does not exclude unavoidable mixing.
[0083] In the method for producing the silane-crosslinked acrylic rubber molded article of the present invention, the steps (2) and (3) are then carried out. In the method for producing a silane-crosslinked acrylic rubber molded product of the present invention, a step (2) is carried out in which the obtained reaction composition is molded to obtain a molded product. This step (2) is sufficient as long as it can mold the reaction composition, and the molding method and molding conditions are appropriately selected depending on the form of the silane-crosslinked acrylic rubber molded product of the present invention or the silane-crosslinked acrylic rubber molded product including the silane-crosslinked acrylic rubber molded product. Examples of the molding method include extrusion molding using an extruder, extrusion molding using an injection molding machine, and molding using other molding machines. Extrusion molding is preferred when the silane-crosslinked acrylic rubber molded product of the present invention or the silane-crosslinked acrylic rubber molded product including the silane-crosslinked acrylic rubber molded product is an electric wire or an optical fiber cable. When step (2) is carried out by extrusion molding, the extrusion speed is not particularly limited, and can be set preferably to a linear speed of 5 to 100 m / min, particularly preferably 10 to 50 m / min. The screw rotation speed of the extruder is not particularly limited, and can be set to usually 15 to 60 rpm, preferably 20 to 40 rpm, taking into consideration the coating layer thickness. In addition, in carrying out the above-mentioned manufacturing method of the present invention, the screw rotation speed set during extrusion molding can be appropriately set to a low rotation speed. A low screw rotation speed is effective when molding thin-walled wiring materials, etc. For example, the rotation speed can be set to 2 to 10 rpm, preferably 2 to 8 rpm.
[0084] In addition, step (2) can be carried out simultaneously with or consecutively to step (c). That is, as one embodiment of the melt mixing in step (c), the molding raw materials can be melt mixed during melt molding, for example, during extrusion molding, or immediately before that. For example, pellets such as dry blends can be mixed together at room temperature (for example, 20 to 25°C) or at a high temperature and introduced (melt mixed) into a molding machine, or they can be melt mixed after mixing, pelletized again, and introduced into a molding machine. More specifically, a series of steps can be adopted in which a molding material consisting of silane MB and silanol condensation catalyst or catalyst MB is melt-kneaded in a coating device, and then extrusion-coated on the outer peripheral surface of a conductor or the like, and molded into a desired shape. In this manner, a molded article of the silane-crosslinkable acrylic rubber composition is obtained. Although partial crosslinking is unavoidable in this molded article, as with the silane-crosslinkable acrylic rubber composition, it is in a partially crosslinked state that retains moldability that allows it to be molded in step (2). Therefore, the silane-crosslinked acrylic rubber molded article of this invention is made into a crosslinked or final crosslinked molded article by carrying out step (3).
[0085] In the method for producing a silane-crosslinked acrylic rubber molded article of the present invention, a step (3) is carried out in which the molded article obtained in the step (2) is brought into contact with water. As a result, the reactive sites of the silane coupling agent capable of silanol condensation are hydrolyzed to silanol groups, and the hydroxyl groups of the silanol groups are condensed with each other by the silanol condensation catalyst present in the molded article, causing a crosslinking reaction. In this way, a silane-crosslinked acrylic rubber molded article in which the silane coupling agent is crosslinked by silanol condensation can be obtained. The treatment in step (3) itself can be carried out by a normal method. Condensation between silane coupling agents proceeds simply by storing at room temperature, for example, 20 to 25°C. Therefore, in step (3), it is not necessary to actively bring the molded body into contact with water. In order to promote this crosslinking reaction, the molded body can also be actively brought into contact with moisture. For example, a method of actively bringing the molded body into contact with water, such as immersion in warm water, immersion in a moist heat bath, or exposure to high-temperature water vapor, can be adopted. In addition, pressure may be applied at this time to allow moisture to penetrate into the interior.
[0086] In this way, a silane-crosslinked acrylic rubber molding is produced from the silane-crosslinkable acrylic rubber composition of the present invention. As described below, this silane-crosslinked acrylic rubber molding contains a crosslinked rubber in which the silane-crosslinkable acrylic rubber is condensed through a siloxane bond. One embodiment of this silane-crosslinked acrylic rubber molding contains a silane-crosslinked rubber and an inorganic filler. Here, the inorganic filler may be bonded to the silane coupling agent of the silane-crosslinked rubber. Therefore, this silane-crosslinked rubber contains at least a crosslinked rubber in which a plurality of crosslinked rubbers are bonded or adsorbed to the inorganic filler by the silane coupling agent, and bonded (crosslinked) through the inorganic filler and the silane coupling agent, and a crosslinked rubber in which the reactive sites of the silane coupling agent of the crosslinkable rubber are hydrolyzed and undergo a silanol condensation reaction with each other, and thus crosslinked through the silane coupling agent. In addition, the silane-crosslinked rubber may contain a mixture of bonds (crosslinks) through the inorganic filler and the silane coupling agent and crosslinks through the silane coupling agent. Furthermore, it may contain a rubber component unreacted with the silane coupling agent and / or a silane-crosslinked acrylic rubber that is not crosslinked.
[0087] Although the details of the reaction mechanism in the production method of the present invention are not yet clear, it is believed to be as follows: When the rubber component is heated and kneaded together with the inorganic filler and the silane coupling agent in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, the organic peroxide decomposes to generate radicals, which cause grafting of the silane coupling agent to the rubber component.
[0088] The heating in step (a-2) also partially induces a reaction to form a chemical bond through a covalent bond between the silane coupling agent and groups such as hydroxyl groups on the surface of the inorganic filler. In the present invention, a final crosslinking reaction may be carried out in step (3). When a specific amount of a silane coupling agent is blended with the base acrylic rubber as described above, it becomes possible to blend a large amount of an inorganic filler without impairing the processability during molding (extrusion moldability), and it is possible to provide mechanical properties and the like while ensuring high-temperature oil resistance.
[0089] In addition, the mechanism of the action of the above process of the present invention is not yet clear, but is presumed to be as follows. That is, by using an inorganic filler and a silane coupling agent before and / or during kneading with the base acrylic rubber, the silane coupling agent bonds with the inorganic filler via a group capable of chemically bonding with the reactive site, and is held by bonding with the uncrosslinked portion (a site capable of grafting reaction) of the rubber component via a group capable of grafting reaction present at the other end. Or, without bonding with the inorganic filler, it is held by being physically or chemically adsorbed to the holes or surface of the inorganic filler. In this way, it is possible to form a silane coupling agent that is strongly bonded to the inorganic filler (the reason for this is thought to be, for example, the formation of a chemical bond with a hydroxyl group or the like on the surface of the inorganic filler) and a silane coupling agent that is weakly bonded to the inorganic filler (the reason for this is thought to be, for example, an interaction due to hydrogen bonding, an interaction between ions, partial charges or dipoles, an action due to adsorption, etc.). In this state, when an organic peroxide is added and kneading is carried out, as described below, the silane coupling agent hardly volatilizes, and the silane coupling agent, which has a different bond with the inorganic filler, undergoes a graft reaction with the rubber component to form a silane-crosslinkable acrylic rubber.
[0090] By the above-mentioned kneading, the silane coupling agent having a strong bond with the inorganic filler among the silane coupling agents maintains the bond with the inorganic filler, and the cross-linking group capable of grafting reacts with the cross-linking site of the rubber component by grafting. In particular, when multiple silane coupling agents are bonded to the surface of one inorganic filler particle through strong bonds, multiple rubber components are bonded through this inorganic filler particle. These reactions or bonds expand the cross-linking network through this inorganic filler. That is, a silane cross-linked acrylic rubber is formed by grafting the silane coupling agent bonded to the inorganic filler to the rubber component.
[0091] In the case of a silane coupling agent having a strong bond with an inorganic filler, the condensation reaction by this silanol condensation catalyst is unlikely to occur in the presence of water, and the bond with the inorganic filler is maintained. The reason why the silanol condensation reaction is unlikely to occur is thought to be that the bond energy between the inorganic filler and the silane coupling agent is very high, and even in the presence of a silanol condensation catalyst, the condensation reaction does not occur. In this way, the rubber component and the inorganic filler are bonded, and the rubber component is crosslinked via the silane coupling agent. This strengthens the adhesion between the rubber component and the inorganic filler, and a molded body with good tensile strength is obtained. In particular, multiple silane coupling agents can be bonded to the surface of one inorganic filler particle, and high tensile strength can be obtained. In this way, the silane coupling agent bonded to the inorganic filler by a strong bond is thought to contribute to high mechanical properties, and in some cases, wear resistance, scratch resistance, etc.
[0092] On the other hand, among the silane coupling agents, the silane coupling agent having a weak bond with the inorganic filler is released from the surface of the inorganic filler, and the crosslinking group of the silane coupling agent, which is a group capable of grafting reaction, reacts with the radical of the rubber component generated by the hydrogen radical abstraction by the radical generated by the decomposition of the organic peroxide, causing a grafting reaction. That is, the silane coupling agent released from the inorganic filler is grafted to the rubber component to form a silane crosslinkable acrylic rubber. The silane coupling agent of the graft portion thus generated is then mixed with a silanol condensation catalyst, and contacts with moisture to cause a condensation reaction (crosslinking reaction). The high-temperature oil resistance of the silane crosslinked acrylic rubber molded body obtained by this crosslinking reaction is increased, making it possible to obtain a silane crosslinked acrylic rubber molded body with excellent high-temperature oil resistance. Furthermore, in some cases, it is possible to impart heat resistance that does not melt even at high temperatures. In this way, the silane coupling agent bonded to the inorganic filler by a weak bond is thought to contribute to improving the degree of crosslinking, that is, improving heat resistance.
[0093] In particular, in the present invention, the crosslinking reaction by condensation using a silanol condensation catalyst in the presence of water in step (3) is carried out after the formation of a molded product, which makes it possible to obtain superior workability in the process up to the formation of a molded product and higher heat resistance than in the past, compared to the conventional method of forming a molded product after the final crosslinking reaction.
[0094] In the present invention, in addition to the high high-temperature oil resistance, mechanical properties, etc. achieved by the above-mentioned silane crosslinking, the silane crosslinked acrylic rubber molded article can be imparted with excellent appearance, mechanical properties, high-temperature oil resistance, and flexibility, and bleeding can also be suppressed. Although the details of how such excellent properties can be imparted to the silane-crosslinked acrylic rubber molded article are not yet clear, it is believed that the base acrylic rubber components work in cooperation with each other as follows. Generally, ethylene-acrylic rubber and mineral oil have very poor compatibility, so simply using them together will cause bleeding. On the other hand, styrene elastomers are easily oiled, and if they are mixed in large quantities, their high-temperature oil resistance will deteriorate. However, in the present invention, by using styrene elastomer and mineral oil in combination with ethylene-acrylic rubber in a specific amount and ratio, the decrease in high-temperature oil resistance due to the mixing of styrene elastomer is suppressed, and the bleeding of mineral oil is also suppressed. Furthermore, it is considered that the softening effect and moldability improvement effect of these components are added, and high-temperature oil resistance, mechanical properties, flexibility, and appearance are achieved in a well-balanced manner.
[0095] Furthermore, according to a preferred embodiment of the present invention, it is possible to impart a higher level of high-temperature oil resistance, heat resistance that does not melt even at high temperatures, flame retardancy, abrasion resistance, etc. Here, heat resistance that does not melt even at high temperatures refers to the property of not melting, preferably at a temperature of 200° C., more preferably at temperatures of 200° C. or higher, and preferably the property of being able to maintain shape or strength, and refers to the elongation rate after heating to 200° C. being 100% or less and the elongation after heating and removal of the load being 25% or less in the hot set test described below.
[0096] The manufacturing method of the present invention can be applied to the manufacture of products (including semi-finished products, parts, and members) that require high-temperature oil resistance, products that require strength in addition to high-temperature oil resistance, products that require flexibility, products that require flame retardancy, components or members of products such as rubber materials, etc. Therefore, a silane-crosslinked acrylic rubber molded body or a silane-crosslinked acrylic rubber molded article including a silane-crosslinked acrylic rubber molded body is considered to be such a product. Examples of the silane-crosslinked acrylic rubber molded product of the present invention, or a silane-crosslinked acrylic rubber molded product containing the silane-crosslinked acrylic rubber molded product, include covering materials for electric wires or flame-retardant cables such as flame-retardant insulated electric wires, rubber substitute materials for electric wires and cables, as well as flame-retardant electric wire parts, flame-retardant heat-resistant sheets, flame-retardant films, etc. Further examples include power plugs, connectors, sleeves, boxes, tape substrates, tubes, sheets, packings, cushioning materials, vibration-proof materials, wiring materials used for internal wiring and external wiring of electric and electronic devices, particularly electric wires and optical cables.
[0097] The manufacturing method of the present invention is particularly suitable for the manufacture of the above-mentioned oil-resistant products, particularly electric wires and optical cables, and can form the covering materials (insulators, sheaths) thereof.
[0098] When the silane-crosslinked acrylic rubber molded article of the present invention or the silane-crosslinked acrylic rubber molded article including the silane-crosslinked acrylic rubber molded article is an extrusion molded article such as an electric wire or cable, the molding material is preferably melt-kneaded in an extruder (extrusion coating device) and subjected to the above-mentioned grafting reaction to prepare a silane-crosslinkable acrylic rubber composition, and the silane-crosslinkable acrylic rubber composition is extruded around the periphery of a conductor or the like to coat the conductor or the like (step (c) and step (2)). At this time, the temperature of the extrusion molding machine is preferably about 120 to 180 ° C. in the cylinder part and about 160 to 210 ° C. in the crosshead part, depending on the various conditions such as the type of rubber and the take-up speed of the conductor. The silane-crosslinked acrylic rubber molded body or the silane-crosslinked acrylic rubber molded article including the silane-crosslinked acrylic rubber molded body can be molded by extrusion coating the silane-crosslinkable acrylic rubber composition containing a large amount of inorganic filler around the conductor or around the conductor with the tensile strength fibers attached or twisted vertically using a general-purpose extrusion coating device without using a special machine such as an electron beam crosslinking machine. For example, the conductor is preferably a metal conductor, and a single wire or twisted wire of soft copper, copper alloy, aluminum, etc. can be used. In addition to bare wires, conductors that are tinned or have an enamel-coated insulating layer can also be used. The thickness of the insulating layer (coating layer made of the silane-crosslinkable acrylic rubber composition of the present invention) formed around the conductor is not particularly limited, but is usually about 0.15 to 5 mm.
[0099] The silane-crosslinked acrylic rubber molded product of the present invention is suitable as a material used in areas requiring oil resistance, particularly high-temperature oil resistance, and can be used to replace acrylic rubber materials that have conventionally been subjected to crosslinking by electron beam irradiation or chemical vulcanization processes, such as not only the covering materials for flame-retardant electric wires and cables, but also hoses, tubes, and even rubber molding materials. It is also effective for members that require flexibility, and can be used, for example, in cab-tire cables, electric wires for automobiles, electric wires for ships, and cables for robots. EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. In Tables 1-1 and 1-2 (collectively referred to as Table 1), the numerical values for the blending amounts of each example are in parts by mass unless otherwise specified. Furthermore, blank spaces for each component mean that the blending amount of the corresponding component is 0 parts by mass.
[0101] In Examples 1 to 18 and Comparative Examples 1 to 10, a part of the rubber component constituting the base acrylic rubber was used as a carrier for the catalyst MB.
[0102] (Examples 1 to 18, Comparative Examples 1 to 7 and 9) First, the inorganic filler, the silane coupling agent, and the organic peroxide were charged in a rotary blade mixer (product name: Mazera PM, manufactured by Mazera Co., Ltd.) in the mass ratio shown in Table 1, and stirred (premixed) at 10 rpm for 1 minute at room temperature (25 ° C.) to obtain a powder mixture (step (a-1)). Next, the obtained powder mixture, the base acrylic rubber, and the antioxidant were charged in the mass ratio shown in Table 1 into a kneader (volume 75 L) previously heated to 100 ° C., mixed at 30 rpm for 5 minutes, and then finished kneaded at 25 rpm for 3 minutes. After confirming that the temperature of the mixture reached 180 to 200 ° C., which is higher than the decomposition temperature of the organic peroxide, the mixture was pelletized using a feeder-ruder and a pelletizer to obtain Silane MB (step (a-2)). The Silane MB thus obtained contains a silane crosslinkable acrylic rubber in which the silane coupling agent has been grafted to the rubber component.
[0103] On the other hand, the base acrylic rubber, inorganic filler, flame retardant, antioxidant and silanol condensation catalyst were sequentially charged in the mass ratios shown in Table 1 into a kneader (volume 75 L) that had been preheated to 80°C, mixed at 30 rpm for 5 minutes, and then finish-kneaded at 25 rpm for 3 minutes. After it was confirmed that the temperature of the mixture had reached about 160°C and the base acrylic rubber had been sufficiently melted, the mixture was pelletized using a feeder-ruder and pelletizer to obtain catalyst MB (step (b)). This catalyst MB is a molten mixture of the carrier and the silanol condensation catalyst.
[0104] Next, Silane MB and Catalyst MB were put into a closed ribbon blender and dry blended for 5 minutes at room temperature (25°C) to obtain a dry blend. At this time, the mixing ratio of Silane MB and Catalyst MB was the mass ratio shown in Table 1. Specifically, in Examples 1 to 4, 6 to 18 and Comparative Examples 1 and 4 to 7, the ratio was 85 parts by mass of the base acrylic rubber of Silane MB and 15 parts by mass of the carrier of Catalyst MB. In Example 5, the ratio was 92 parts by mass of the base acrylic rubber of Silane MB and 8 parts by mass of the carrier of Catalyst MB. In Comparative Examples 2, 3, and 9, the ratio was 95 parts by mass of the base acrylic rubber of Silane MB and 5 parts by mass of the carrier of Catalyst MB.
[0105] Next, an extruder equipped with a screw having a screw diameter of 25 mm and an L / D (ratio of effective screw length L to diameter D) of 25 was set to a die temperature of 200° C., and extrusion temperature conditions for the following feeders were set as follows: C3 = 180° C., C2 = 150° C., and C1 = 130° C. The prepared dry blend was put into this extruder and melt-mixed (step (c)). The mixture was extruded and coated onto a bare soft copper wire conductor having a diameter of 0.8 mm at a linear speed of 7 m / min and a screw rotation speed of 10 rpm (extrusion molding condition (1), conditions of appearance test (1)) so that the outer diameter was 1.4 mm and the insulation layer thickness was 0.3 mm, or at a linear speed of 7 m / min and a screw rotation speed of 35 rpm (extrusion molding condition (2), conditions of appearance test (2)) so that the outer diameter was 2.4 mm and the insulation layer thickness was 0.8 mm, to obtain a coated conductor (step (2)). The dry blend was melt-mixed in an extruder before extrusion (step (c)) to prepare a silane-crosslinkable acrylic rubber composition as a reaction composition. This silane-crosslinkable acrylic rubber composition is a melt mixture of silane MB and catalyst MB, and contains the above-mentioned silane-crosslinkable acrylic rubber.
[0106] The obtained coated conductor was left for 24 hours under the conditions of room temperature (23°C) and 50% RH to hydrolyze the reactive sites (trialkoxysilyl groups) of the silane coupling agent, followed by a silanol condensation reaction (silane crosslinking) (step (3)). In this manner, each electric wire in which the conductor was coated with a silane-crosslinked acrylic rubber molded body was produced under the above-mentioned extrusion molding conditions (1) and (2). The silane-crosslinked acrylic rubber molded body as the coating layer had the above-mentioned silane-crosslinked acrylic rubber.
[0107] Comparative Example 8 An electric wire was manufactured in the same manner as in Example 1, except that when preparing Silane MB, the inorganic filler, silane coupling agent, and organic peroxide were not premixed (step (a-1)), and the components shown in the Silane MB column in Table 1 were added to a kneader in the mass ratio shown in Table 1 to obtain Silane MB.
[0108] Comparative Example 10 An electric wire was produced in the same manner as in Example 1, except that the components shown in the Silane MB column of Table 1 were charged into a kneader in the mass ratio shown in Table 1 to obtain Silane MB.
[0109] In the production of the above examples and comparative examples, when premixing of the inorganic filler, the silane coupling agent, and the organic peroxide (step (a-1)) was performed, it is recorded as "Yes" in the "Premixing" column of Table 1, and when premixing was not performed, it is recorded as "No".
[0110] The components shown in Table 1 were as follows. (1) Ethylene-acrylic rubber 1: Baymac Ultra HT-OR (product name, manufactured by DuPont, terpolymer) (2) Ethylene-acrylic rubber 2: Baymac DP (trade name, manufactured by DuPont, binary copolymer) (3) Ethylene resin 1: Evolu SP3010 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, density 0.926 g / cm 3 ) (4) Ethylene resin 2: Evolu SP4020 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, density 0.937 g / cm 3 ) (5) Ethylene resin 3: Levaprene 800 (trade name, manufactured by LANXESS, ethylene-vinyl acetate copolymer resin (EVA)) (6) Ethylene resin 4: Evolue SP1540 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, density 0.913 g / cm 3 ) (7) Styrene elastomer 1: Tuftec N504 (product name, manufactured by Asahi Kasei Corporation) (8) Mineral oil 1: Cosmo Neutral 500 (product name, Cosmo Oil Lubricants, paraffin oil) (9) Propylene resin 1: PB222A (product name, manufactured by SunAllomer Co., Ltd., propylene resin) (10) Modified polyethylene 1: Adtex L6100M (product name, manufactured by Japan Polyethylene Corporation, unsaturated carboxylic acid modified polyethylene (unsaturated carboxylic acid is maleic acid)) (11) Inorganic filler 1: Kisuma 5L (product name, manufactured by Kyowa Chemical Industry Co., Ltd., magnesium hydroxide) (12) Inorganic filler 2: Aerosil 200 (product name, manufactured by Nippon Aerosil Co., Ltd., silica) (13) Flame retardant 1: Nova Red 120UFA (product name, manufactured by Rinkagaku Kogyo, red phosphorus) (14) Silane coupling agent 1: KBM-1003 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., vinyltrimethoxysilane) (15) Organic peroxide 1: Perhexa 25B (trade name, NOF Corp., 2,5-dimethyl-2,5-di(t-butylperoxy)hexane) (16) Antioxidant 1: Irganox 1076 (trade name, manufactured by BASF, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (17) Silanol condensation catalyst 1: Adeka STAB OT-1 (trade name, manufactured by ADEKA Corporation, dioctyltin dilaurate)
[0111] The following tests were carried out on each of the produced electric wires, and the results are shown in Table 1.
[0112] 1. Appearance test (1) When manufacturing electric wires by extrusion molding under the above-mentioned extrusion molding conditions (1) (insulation layer thickness 0.3 mm), the case where no roughness such as gel particles is observed on the surface of the electric wire is rated as "A (high quality)", the case where there are no roughness such as large gel particles exceeding 1 mm in diameter on the surface of the electric wire, but 1 to 5 roughness such as gel particles less than 1 mm in diameter are observed on the surface of the electric wire is rated as "B (good)", and the case where there is 1 or more roughness such as large gel particles exceeding 1 mm in diameter on the surface of the electric wire or 6 or more roughness such as gel particles less than 1 mm in diameter on the surface of the electric wire is rated as "D (fail)". In this test, the screw rotation speed is slower than that in the appearance test (2) described below, and the test is conducted under conditions that make it easier for roughness such as gel particles to form.
[0113] 2. Appearance test (2) When manufacturing electric wires by extrusion molding under the above-mentioned extrusion molding condition (2) (insulation layer thickness 0.8 mm), the case where no roughness such as gel particles was observed on the surface of the electric wire was rated as "A (high quality)", the case where 1 to 5 roughness such as gel particles were observed on the surface of the electric wire was rated as "B (good)", and the case where 6 or more roughness such as gel particles were observed on the surface of the electric wire was rated as "D (fail)".
[0114] 3. Bleeding test The electric wire obtained under the above extrusion molding condition (2) was left in a thermostatic chamber at 60°C for 14 days, and then left at room temperature (23°C) for 24 hours, and the appearance of the electric wire was visually observed. Those in which no oil bleeding was observed were rated "A (pass)", and those in which bleeding was observed were rated "D (fail)".
[0115] 4. Tensile properties (mechanical properties) A tensile test was carried out on the coating (tubular piece) taken out from each electric wire produced using the coated conductor obtained under the above extrusion molding condition (2). This tensile test was performed in accordance with JIS C 3005, with a gauge length of 25 mm and a tensile speed of 200 mm / min, and the tensile strength (MPa) and tensile elongation (%) were measured. Tensile strength of 8 MPa or more was given an excellent level of "A", 6 MPa or more and less than 8 MPa was given a "B" as a pass level for this test, 4.5 MPa or more and less than 6 MPa was given a "C" as a pass level for this test, and less than 4.5 MPa was given a "D" as a fail level for this test. Tensile elongation of 125% or more was given an excellent level and was designated an "A", 100% or more but less than 125% was given a pass level and was designated a "B", 80% or more but less than 100% was given a pass level and was designated a "C", and less than 80% was given a fail level and was designated a "D".
[0116] 5. Flexibility test (100% modulus) The tensile stress at 100% elongation (100% modulus) was measured using the tensile property test method. A 100% modulus of less than 8 MPa was rated as an excellent level "A," a level between 8 MPa and 9 MPa was rated as a good level "B," a level between 9 MPa and 10 MPa was rated as an acceptable level "C," and a level of 10 MPa or more was rated as a failing level "D."
[0117] 6-1.Oil resistance test A For each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2), the "oil resistance test" described in JIS C 3005 was performed. In the oil resistance test A, the oil immersion temperature was 100°C, the oil immersion time was 24 hours, and IRM903 was used as the oil. The tensile strength and tensile elongation after oil immersion were measured under the same conditions as in the above tensile property test. The tensile strength retention rate (%) was calculated by dividing the tensile strength after oil immersion by the tensile strength before oil immersion (the tensile strength obtained in the above tensile test). The tensile elongation retention rate (%) was calculated in the same manner. The evaluation of this test was as follows: if the retention of tensile strength and tensile elongation before and after oil immersion were both 80% or more, it was given an excellent level of "A", if the retention of tensile strength and tensile elongation were both 70% or more and less than 80%, it was given a good level of "B", if the retention of tensile strength and tensile elongation were both 60% or more and less than 70%, it was given a passing level of "C", and if either the retention of tensile strength or tensile elongation was less than 60%, it was given a failing level of "D".
[0118] Furthermore, each wire was evaluated for the following desirable properties.
[0119] 6-2.Oil resistance test B For each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2), the "oil resistance test" described in JIS C 3005 was performed. In the oil resistance test B, the oil immersion temperature was 100°C, the oil immersion time was 48 hours, and IRM903 was used as the oil. The tensile strength and tensile elongation after oil immersion were measured under the same conditions as in the above tensile property test. The tensile strength retention rate (%) was calculated by dividing the tensile strength after oil immersion by the tensile strength before oil immersion (the tensile strength obtained in the above tensile test). The tensile elongation retention rate (%) was calculated in the same manner. The evaluation of this test was as follows: if the retention of tensile strength and tensile elongation before and after oil immersion were both 80% or more, it was given an excellent level of "A", if the retention of tensile strength and tensile elongation were both 70% or more and less than 80%, it was given a good level of "B", if the retention of tensile strength and tensile elongation were both 60% or more and less than 70%, it was given a passing level of "C", and if either the retention of tensile strength or tensile elongation was less than 60%, it was given a failing level of "D".
[0120] 6-3.Oil resistance test C For each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2), the "oil resistance test" described in JIS C3005 was performed. In the oil resistance test C, the oil immersion temperature was 100°C, the oil immersion time was 72 hours, and IRM903 was used as the oil. The tensile strength and tensile elongation after oil immersion were measured under the same conditions as in the above tensile property test. The tensile strength retention rate (%) was calculated by dividing the tensile strength after oil immersion by the tensile strength before oil immersion (the tensile strength obtained in the above tensile test). The tensile elongation retention rate (%) was calculated in the same manner. The evaluation of this test was as follows: if the retention of tensile strength and tensile elongation before and after oil immersion were both 80% or more, it was given an excellent level of "A", if the retention of tensile strength and tensile elongation were both 70% or more and less than 80%, it was given a good level of "B", if the retention of tensile strength and tensile elongation were both 60% or more and less than 70%, it was given a passing level of "C", and if either the retention of tensile strength or tensile elongation was less than 60%, it was given a failing level of "D".
[0121] 6-4.Oil resistance test D For each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2), the "oil resistance test" described in JIS C3005 was performed. In the oil resistance test D, the oil immersion temperature was 100°C, the oil immersion time was 168 hours, and IRM903 was used as the oil. The tensile strength and tensile elongation after oil immersion were measured under the same conditions as in the above tensile property test. The tensile strength retention rate (%) was calculated by dividing the tensile strength after oil immersion by the tensile strength before oil immersion (the tensile strength obtained in the above tensile test). The tensile elongation retention rate (%) was calculated in the same manner. The evaluation of this test was as follows: if the retention of tensile strength and tensile elongation before and after oil immersion were both 80% or more, it was given an excellent level of "A", if the retention of tensile strength and tensile elongation were both 70% or more and less than 80%, it was given a good level of "B", if the retention of tensile strength and tensile elongation were both 60% or more and less than 70%, it was given a passing level of "C", and if either the retention of tensile strength or tensile elongation was less than 60%, it was given a failing level of "D".
[0122] 7.Hot set test A hot set test was carried out using tubular pieces prepared in the same manner as for each electric wire produced using the coated conductor obtained under the above extrusion molding condition (2). The hot set test was performed according to the method described in IEC 60811-2-1. The test conditions were 200°C, heating time 15 minutes, and load 20 N / cm. 2 The length after heating was measured, and the elongation percentage (%) relative to the length before heating was calculated. Furthermore, the load was removed, and the length after the load was removed was measured, and the elongation percentage (%) relative to the length before heating was calculated. If the elongation rate after heating was 100% or less and the elongation rate after heating and removing the load was 25% or less, the test was deemed to pass and given a grade of "A." Any other grade was deemed to fail and given a grade of "D."
[0123] 8.Flame Retardancy Test A flame retardancy test was carried out on each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2) based on the single-strand flame test specified in IEC (International Electronic Commission) 60332-1-2. A 600mm long sample was cut from the wire, held vertically, and a burner flame was applied to the bottom of the sample at a 45 degree angle and burned for 60 seconds. After the burner was removed and the flame had gone out, if the distance between the top of the carbonized part and the upper support member was 50mm or more, it was rated as "A", and if it was less than 50mm, it was rated as "D".
[0124] [Table 1-1]
[0125] [Table 1-2]
[0126] In the manufacturing method having each step specified in the present invention, when a base acrylic rubber not satisfying the composition specified in the present invention is mixed, any one of the appearance test (1), the bleeding test, the mechanical property test, the flexibility test, and the oil resistance test A is failed, and a silane crosslinked acrylic rubber molded body having excellent appearance, mechanical properties, flexibility, and high-temperature oil resistance and suppressed bleeding could not be produced (Comparative Examples 1 to 8). When the inorganic filler and the silane coupling agent are not premixed, the mechanical property test (tensile strength) and the oil resistance test A are failed, and a silane crosslinked acrylic rubber molded body having excellent appearance, mechanical properties, flexibility, and high-temperature oil resistance and suppressed bleeding could not be produced (Comparative Example 9). Furthermore, when the components necessary for silane crosslinking are not blended, the oil resistance test A is failed, and a silane crosslinked acrylic rubber molded body having excellent appearance, mechanical properties, flexibility, and high-temperature oil resistance and suppressed bleeding could not be produced (Comparative Example 10). In contrast, in a manufacturing method having each step specified in the present invention, when a base acrylic rubber satisfying the composition specified in the present invention is mixed with an inorganic filler, an organic peroxide, etc. in a specific amount, it is possible to manufacture a silane-crosslinked acrylic rubber molded article that passes all of the appearance test (1), the bleeding test, the mechanical property test, the flexibility test, and the oil resistance test A, and has excellent appearance, mechanical properties, flexibility, and high-temperature oil resistance, and has suppressed bleeding (Examples 1 to 18). Therefore, all of the electric wires of Examples 1 to 18 that have these molded articles as coating layers have excellent appearance, mechanical properties, flexibility, and high-temperature oil resistance, and has suppressed bleeding. Furthermore, since they pass the appearance test (1) and the appearance test (2), it is understood that they can be adapted to changes in the screw rotation speed. From the above, it can be seen that the present invention is capable of producing molded articles for various applications, including thin-walled molded articles, in addition to electric wires.
Claims
1. A method for producing a silane-crosslinked acrylic rubber molded product, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.6 parts by mass of an organic peroxide, 1 to 200 parts by mass of an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a graft reaction site capable of undergoing a graft reaction with the base acrylic rubber in the presence of a radical generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of a base acrylic rubber, and grafting the graft reaction site with a site capable of undergoing a graft reaction of the base acrylic rubber by the radical generated from the organic peroxide, thereby obtaining a silane crosslinkable acrylic rubber composition containing a silane crosslinkable acrylic rubber. Step (2): A step of molding the silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked acrylic rubber molded product. the base acrylic rubber contains 20 to 85% by mass of ethylene-acrylic rubber, 60% by mass or less of ethylene resin, 1 to 20% by mass of styrene elastomer, and 1 to 20% by mass of mineral oil, such that the ratio of the content of the styrene elastomer to the content of the mineral oil (content of styrene elastomer:content of mineral oil) is 1:2.5 to 1:0.5 by mass, In carrying out the step (1), A method for producing a silane-crosslinked acrylic rubber molded product, wherein in the case where the entirety of the base acrylic rubber is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), and (c), and in the case where only a part of the base acrylic rubber is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), (b), and (c). Step (a-1): A step of mixing the inorganic filler and the silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and all or a part of the base acrylic rubber in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause a graft reaction between the graft reaction site and a graft reaction site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): A step of melt-mixing the remainder of the base acrylic rubber and the silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch and the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable acrylic rubber composition.
2. The ethylene resin has a viscosity of 0.910 to 0.940 g / cm 3 2. The method for producing a silane-crosslinked acrylic rubber molded article according to claim 1, wherein the resin is an ethylene-α-olefin copolymer resin, an ethylene-vinyl acetate copolymer resin, or a mixture thereof having a density of 100 to 2000 g / mol.
3. The method for producing a silane-crosslinked acrylic rubber molded article according to claim 1 or 2, wherein the base acrylic rubber contains 1 to 6 mass % of a propylene resin.
4. The method for producing a silane-crosslinked acrylic rubber molded article according to any one of claims 1 to 3, wherein the inorganic filler is blended in an amount of 30 to 200 parts by mass per 100 parts by mass of the base acrylic rubber.
5. The method for producing a silane-crosslinked acrylic rubber molded article according to any one of claims 1 to 4, wherein the silanol condensation catalyst is blended in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the base acrylic rubber.
6. The method for producing a silane-crosslinked acrylic rubber molded article according to any one of claims 1 to 5, wherein the ethylene-acrylic rubber comprises a binary copolymer of ethylene and an alkyl acrylate ester, or a ternary copolymer of ethylene, an alkyl acrylate ester, and a copolymerization component containing a carboxy group, or a mixture thereof.
7. The method for producing a silane-crosslinked acrylic rubber molded article according to any one of claims 1 to 6, wherein the inorganic filler is a metal hydrate.
8. The method for producing a silane-crosslinked acrylic rubber molded product according to any one of claims 1 to 7, wherein in the step (1), 30 to 180 parts by mass of the inorganic filler, 1 to 15 parts by mass of the silane coupling agent, 0.01 to 0.6 parts by mass of the organic peroxide, and 0.01 to 0.5 parts by mass of the silanol condensation catalyst are melt-mixed with respect to 100 parts by mass of the base acrylic rubber.
9. A silane-crosslinkable acrylic rubber composition produced by the step (1) of the production method according to any one of claims 1 to 8.
10. A silane-crosslinked acrylic rubber molded article produced by the method for producing a silane-crosslinked acrylic rubber molded article according to any one of claims 1 to 8.
11. A silane-crosslinked acrylic rubber molded article comprising the silane-crosslinked acrylic rubber molded article according to claim 10.
Citation Information
Patent Citations
Heat-resistant silane crosslinked resin molding and heat-resistant silane crosslinkable resin composition and method for producing them, silane master batch and heat-resistant product
JP2016188307A
Silane crosslinked acrylic rubber molded body and manufacturing method therefor, silane crosslinked acrylic rubber composition, and oil resistant product
JP2019116582A